Islamic Education Model during the Leadership of Khulafaur Rasyidin - Hoktaviandri; Mislaini; Rori Afrinaldi (Al Bahri: Journal of Islamic Education, 2024)
This study examines the model of Islamic education during the leadership of Khulafaur Rasyidin. Islamic education, which is based on the Qur'an and Sunnah, aims to form human beings who believe and fear Allah SWT. During this period, the caliphs paid great attention to education and the dissemination of knowledge. The research method used is literature research, by collecting data from various relevant literature. Every caliph, ranging from Abu Bakr Ash-Siddiq, Umar bin Khattab, Uthman bin Affan, to Ali bin Abi Talib, has unique contributions and strategies in developing Islamic education. Despite facing political and social challenges, they succeeded in strengthening the foundation of Islamic education which includes aspects of monotheism, morals, worship, and health. This research is important as a reference in understanding the development of Islamic education and as a source of ideas in developing Islamic education strategies today. Key words: Islamic education, Khulafaur Rasyidin